VISUALIZATION OF SOLVED PROBLEM AT THE TEACHING OF TECHNICAL MECHANICS - MONKOVÁ, Katarína; HLOCH, Sergej; MIŠÍK, Ladislav (Trends in education, 2009)
The article deals with visualization of solved problem at the Technical mechanics teaching as supporting tool of specific topic interpretation. It shows the possibilities of CAD/CAM system using within such subjects that unrelated with design and 3D modelling at the first sight. Article is direct supported from grant KEGA no.3/5173/07 of Cultural and Educational Grant Agency of Ministry of Education of Slovak republic.
Keywords: visualization; CAD/CAM system; mechanism.